Combined effect of pulsed electric field and osmotic dehydration pre-treatments on mass transfer and quality of air dried goji berry. (October 2018) - Dermesonlouoglou, E.; Chalkia, A.; Dimopoulos, G.; Taoukis, P.
Abstract: Pulsed electric field (PEF) and osmotic dehydration (OD) pre-treatments can improve the slow and energy intensive process of goji berry drying. The effect of PEF and OD processing conditions on mass transfer, color, antioxidant capacity and total phenolic content was studied. Application of PEF (0.9–2.8 kV/cm, up to 7500 pulses) caused tissue permeabilization (electrical conductivity disintegration index, Z p, value up to 0.38, due to the structure of goji berry waxy peel) and significantly enhanced mass transfer during subsequent OD and air drying (increased effective diffusivity coefficients D ew and D es and drying rate k drying respectively). Combining OD (55 °C, 60 min), PEF (2.8 kV/cm, 750 p ) and air drying (60 °C) compared to conventional air drying led to total processing time decrease (by 180 min or 33%), better color retention, higher antioxidant capacity and total phenolic content. Highlights: Goji berry was treated by pulsed electric field, osmotically dehydrated and dried. Application of PEF enhanced mass transfer rates during subsequent OD. Application of PEF and OD increased drying rate and decreased drying time. PEF allowed dried goji berry to retain quality (color, antioxidants, phenolics). PEF-OD can be used for the production of novel dried goji berry products.